2020
DOI: 10.5430/ijh.v6n2p54
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviors among Syrian refugee women: A scoping review

Abstract: Objective: The aim of this scoping review was to explore what is known about the health seeking behaviors among Syrian refugee women within hospital and community settings. The objectives were to explore health seeking behaviors of Syrian refugee women and highlight specific issues that are important to Syrian refugee women related to seeking for health care. In addition, to uncover potential obstacles/barriers that face Syrian refugee women while seeking for health care.Methods: Arksey and O’Malley (2005) fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Gender-related social and cultural issues, such as social roles and expectations for men and women, can vary greatly from country to country, which can exacerbate disparities in health and access to healthcare. Men, for instance, do not permit their female patients to be consulted or treated by men in some societies (Al-hamad et al, 2020;Guruge et al, 2018). As a result, a study on refugees' access to healthcare revealed that in Norway, immigrants prefer to see doctors (Mbanya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gender-related social and cultural issues, such as social roles and expectations for men and women, can vary greatly from country to country, which can exacerbate disparities in health and access to healthcare. Men, for instance, do not permit their female patients to be consulted or treated by men in some societies (Al-hamad et al, 2020;Guruge et al, 2018). As a result, a study on refugees' access to healthcare revealed that in Norway, immigrants prefer to see doctors (Mbanya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the challenges of migration and resettlement hindered them from taking appropriate correct choices in relation to their health (Kiselev et al., 2020). A scoping review on health seeking behaviours of Syrian refugees conducted on 19 studies revealed that socio‐cultural, language, social disconnection, lack of public transportation and the lack of culturally and gender specific health services were common barriers for accessing healthcare services (Al‐Hamad, Forchuk, Oudshoorn, & McKinley, 2020). This study aiming to identify the responsibility of Syrian refuges in promoting their health.…”
Section: Introductionmentioning
confidence: 99%